The Spillover Effect of Shocks of Fundamental Factors and Speculative Activity on Prices Volatility of World Vegetable Oil - Fitrianti, Wanti; Syaukat, Yusman; Hartoyo, Sri; Fariyanti, Anna (International Journal of Economics and Financial Issues, 2019)
This study is aimed to precisely measure the persistence and the spillover effect of shocks of fundamental factors and speculative activity on the volatility of world vegetable oil prices. This study is analyzed using GARCH and VAR Model substantially continued by Generalized Impulse Response Function (GIRF) and Forecast Error Variance Decomposition (FEVD). This study uses monthly secondary data from January 2004 to June 2017. The main findings of this study indicate that there are the persistence of volatility in prices of palm oil, soybean oil and rapeseed oil and bidirectional volatility spillovers between vegetable oils. The study also finds the volatility of palm oil prices to become the largest transmitter of volatility in the prices of other vegetable oils. In the long term, it shows the magnitude of the effect of demand shocks especially GDP growth and speculative in relation hedging activity on reducing the prices volatility of vegetable oil. Keywords: price, shock, speculative, vegetable oil, volatility JEL Classifications: E30, F17, F40, Q02, Q17 DOI: https://doi.org/10.32479/ijefi.7621